Pengaruh Penambahan Minyak Nabati pada Media Tumbuh terhadap Pertumbuhan Cendawan Entomopatogen Lecanicillium lecanii - Yuliani, Desi; Sugiarto, Sugiarto; Afifah, Lutfi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Pest attacks are one of the challenges frequently encountered in rice cultivation. Effective and environmentally friendly control can be achieved with the entomopathogenic fungus Lecanicillium lecanii. The addition of vegetable oils such as peanut oil and castor oil can enhance the growth and development of the entomopathogenic fungus. This study aims to find the corn growth medium with the addition of vegetable oils that provides the best effect for the growth of the entomopathogenic fungus L. lecanii. The method used is a Completely Randomized Design (CRD) with a single factor consisting of 7 treatments with 4 replications: Control (Corn Medium); T1 (Corn + Peanut Oil 2 ml); T2 (Corn + Peanut Oil 5 ml); T3 (Corn + Peanut Oil 10 ml); J1 (Corn + Castor Oil 2 ml); J2 (Corn + Castor Oil 5 ml); J3 (Corn + Castor Oil 10 ml). The results of this study indicate that the addition of vegetable oils to the corn growth medium has a significant effect on the growth of the entomopathogenic fungus L. lecanii. The most effective growth medium for L. lecanii is corn medium + 10 ml peanut oil, providing an incubation period of 1 days and a colony diameter of 8.00 cm.